Measuring Physical Fitness among Secondary School Students of ages between 10 to 15 Years - Masood Mafooz, a Muhammad Tahir NazeerQasid Naveed, Muhammad Badar Habib2, Badar Mohy ud Din, Muhammad Zia ul Haq, (Opción)
Physical inactivity globally problem whereby a large number of the population do not take part in the sports and physical activity in order to increase health benefits. Sedentary behavior is a primary risk factor among children. The main purpose of the study was to measure the norm of physical efficiency test among students aged 10 to 15 years. Methods: The total of 506 students participated in the study aged between 10 to 15 Years. They were regularly participating in physical activity and sports in their daily routine life. The norms of physical efficiency test were used for collecting data from the male students. The age, endurance, speed, muscular strength, explosive strength, and agility of all subjects were measured. Results: On the base of analysis of the study the strength of students ages between of 10-15 years were almost half of the students standing broad jump range was between 5-6 feet while almost onethird of the students were range between 4-5 feet. Conclusion: This study expressed that the norms of the physical efficiency test is valid and reliable to assess the level of fitness among the students. Future research can use these instruments for measuring the level of fitness among the participants.